Ethnobotany, Pharmacology and Major Bioactive Metabolites from Impatiens Genus Plants and their Related Applications - Delgado-Rodríguez, Fabián Vinicio; Weng-Huang, Nien Tzu; Gutiérrez, Arlene Loría; Arias-Núñez, David; Rosales-Leiva, Christopher (Pharmacognosy Reviews)
Impatiens genus comprises several species important for agriculture and food industries, ethnobotany, and research in pharmacology, phytochemistry, biotechnology and pharmaceutical sciences. In this paper, a systematic review of ethnobotanical uses, bioactivities discovered, and research applications reported for Impatiens plants and their major bioactive constituents are presented aiming to provide an integrative comprehension of relevance of the genus in the mentioned fields and to give guidance for the further research of unexplored or poorly investigated species of this genus. Through this review, an update on this expanding area of research is also provided. According to revisited information, most of bioactive compounds are phenolics, phytosterols, triterpenoids, and peptides. There is a wide spectrum of applications investigated for Impatiens plants extracts and their bioactive metabolites, however, in most cases, they are related to their antimicrobial, cytotoxic, anti-inflammatory, anti-anaphylactic, and antioxidant properties. Further efforts are needed to evaluate the efficacy and safety of Impatiens plants extracts and bioactive compounds to get a complete perspective of their potential applications. Most plants from Impatiens genus with ethnobotanical interests have been poorly studied, therefore, more research of them will be useful to validate their use, to verify their safety and to isolate their main bioactive compounds.
Keywords: Impatiens; Ethnobotany; Bioactivities; Metabolites; Toxicity; Applications